QUESTIONING THE ROLE OF THE EXECUTIVE HOUSEKEEPER IN IMPROVING THE PERFORMANCE OF HOUSEKEEPING STAFF: A CASE STUDY AT NOVOTEL MANADO GOLF RESORT AND CONVENTION CENTER - Vesty Sambeka; Linda Sinolungan; Silvana Wewengkang; Meiske Sangian; Fonny Sangari; Maria Manggribeth (PT. Jurnal Center Indonesia Publisher, 2026)
The Executive Housekeeper is a member of management responsible for ensuring comfort both in guest rooms and for all staff under their command, namely Room Attendants and Public Area staff as this directly impacts staff performance. However, the ideal conditions expected at the Novotel Manado Golf Resort and Convention Center do not always materialize; staff performance sometimes declines, and this is believed to stem from leadership failing to provide adequate support for their subordinates’ work. The purpose of this study is to analyze the role of the executive housekeeper in improving the performance of housekeeping employees at the Novotel Manado Golf Resort and Convention Center. The research method employed by the researcher is qualitative field research, as the data obtained consists of descriptive accounts. Data collection was conducted through interviews with 9 staff members in the housekeeping department. The collected data was then analyzed using qualitative analysis.